Answer:
Balanced chemical equation:
2Al + 3H₂SO₄ → Al₂(SO₄)₃ + 3H₂
Step-by-step explanation:
Chemical equation:
Al + H₂SO₄ → Al₂(SO₄)₃ + H₂
Balanced chemical equation:
2Al + 3H₂SO₄ → Al₂(SO₄)₃ + 3H₂
Steps:
Let balance the SO₄ first.
Al + 3H₂SO₄ → Al₂(SO₄)₃ + H₂
There are three H₂ on left so put the coefficient three on right too.
Al + 3H₂SO₄ → Al₂(SO₄)₃ + 3H₂
Two Al on right and one on left so we will put the coefficient two on left.
2Al + 3H₂SO₄ → Al₂(SO₄)₃ + 3H₂
All atoms are correctly balanced.